Changes of Alcohol Control Law in Online Media: A Case Study - Kalinkaitė, Vaida (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English]Political science and mass communication studies have proven long ago that media outlets can affect public opinion. This is especially important when political choices are made. The media can determine how the public will react to changes. In our case, we delve into a potential threat of a biased public opinion (favorable to certain business subjects, politicians or others parties) being formed. This relates to the media outlets or organizations stepping over the boundaries of ethics for a chance to make a profit from certain interested individuals, organizations or companies.This study addresses the problem of how the changes in the legislation of alcohol control have been reflected in the Lithuanian online newspapers 15min.lt, Delfi.lt and Lrytas.lt. Our study object pertains to how the changes in the law of alcohol control are being reflected. The aim of this article is to examine how these changes of law have been reflected in Lithuanian media.A qualitative case study was conducted using content analysis. The results of the research show that the abovementioned Lithuanian online newspapers reflected a rather one-sided evaluation of the law changes. Most of the changes were reflected in a negative way; there were more negative than positive publications informing about the changes.Although similar tendencies have been identified in all the online newspapers, Lrytas.lt happened to stand out. There were publications that had no clear sources of information; the authors of the publications were not mentioned as well. Furthermore, there were publications criticizing not the changes themselves but certain members of the parliament. The appliance of ethical norms was deemed to be more characteristic of Delfi.lt and 15min.lt.
Keywords: alcohol control law in Lithuania; news framing; agenda setting theory; alcohol control law in media